Mental health in Nigeria: A Neglected issue in Public Health - Yusuf Hassan Wada; Linu Rajwani; Emmanuel Anyam; Evelyn Karikari; Mitchelle Njikizana; Lilian Srour; Garba M. Khalid (Elsevier, 2021)
In Nigeria, the disparity between available healthcare services and need for mental health services is palpable. Although, the country has made significant advances on challenging public health problems, health-related policy development and legislation in trying to achieve health for all policy, there have been challenges with regards to mental health services including that of policy development and legislation, financing, research, training and integration of mental health care into primary health care. We consulted relevant publications, official document, policy statement, blueprints, working plans of the relevant organizations responsible for mental care and services locally and globally. We identify and highlight challenges faced in mental health services implementation and provide recommendations as way forward and call for urgent action to government, non-governmental organizations (NGOs), policy makers and legislatives which are urgently needed to reform and implement them for a better, accessible, and affordable mental health services for the mental well-being of the populace.